Media Rituals and Patriarchal Legitimacy in Indonesian Folklore: A Comparative Regional Analysis - Aurelius Ratu; Yuni Setyaningsih; Rumaysha Gikha Nisrina; Eka Dian Savitri (Universitas Andalas, 2026)
Drawing on Nick Couldry’s notion of media rituals, this study conceptualizes folklore as a symbolic practice that reinforces masculine authority through the repetition of narratives. Employing a qualitative approach, 204 folktales from Sumatra, Java, Kalimantan, Sulawesi, Bali, and Eastern Indonesia were analyzed using MAXQDA-assisted coding. The findings reveal consistent patterns across regions: male characters such as kings, princes, and fathers are positioned as leaders and centers of power, while female figures are largely confined to domestic, sacred, or passive roles. Nonetheless, regional variations emerge. In Kalimantan, narratives allow greater space for female agency, whereas in Java and Sumatra patriarchal structures are reproduced in explicitly political and hierarchical forms. These results indicate that folklore not only reproduces gender hierarchies but also constitutes a contested arena in which counter-rituals can open possibilities for alternative interpretations. Recasting female figures as active and autonomous agents provides a means of questioning patriarchal dominance and constructing more inclusive gender narratives. This research advances scholarship in folklore and gender studies by mapping the regional dynamics of patriarchal legitimization in Indonesia and demonstrating reinterpretation as a cultural strategy for transformation